MEASURING THE IMPACT OF INFLATIONARY PRESSURES ON FOREIGN TRADE IN AGRICULTURAL COMMODITIES AND LIVE ANIMALS: A CASE STUDY OF IRAQ - N. M. Kokaz; S. A. Hammad (مجلة الأنبار للعلوم الزراعية, 2025)
This paper investigated the impact of inflationary pressures on foreign trade in agricultural commodities and live animals for the Iraqi economy for 2004-2022. The standard vector error correction model (VECM) was used to estimate the relationship between the variables. The results showed a long-term equilibrium relationship between the inflationary pressures variable (X) and the trade balance in agricultural commodities and live animals (Y), meaning there is a long-term equilibrium causal relationship between the two variables. The results indicate the presence of a positive effect (direct relationship) between the two variables in the long run. Achieving monetary stability will increase the value of the agricultural trade balance. The paper recommends that monetary policy should aim to control the rate of money supply (money supply) to limit the high rates of inflation and make its growth rate parallel that of the gross domestic product to achieve monetary stability. This would support a higher growth in agricultural production and raise the competitiveness of local products for export as well as reduce agricultural imports to achieve balance in its trade balance